Strain Driven Conducting Domain Walls in a Mott Insulator. (17th July 2022) - Puntigam, Lukas; Altthaler, Markus; Ghara, Somnath; Prodan, Lilian; Tsurkan, Vladimir; Krohns, Stephan; Kézsmárki, István; Evans, Donald M.
Abstract: Rewritable nanoelectronics offer new perspectives and potential to both fundamental research and technological applications. Such interest has driven the research focus into conducting domain walls: pseudo‐2D conducting channels that can be created, positioned, and deleted in situ. However, the study of conductive domain walls is largely limited to wide‐gap ferroelectrics, where the conductivity typically arises from changes in charge carrier density, due to screening charge accumulation at polar discontinuities. This work shows that, in narrow‐gap correlated insulators with strong charge‐lattice coupling, local strain gradients can drive enhanced conductivity at the domain walls—removing polar‐discontinuities as a criteria for conductivity. By combining different scanning probe microscopy techniques, it is demonstrated that the domain wall conductivity in GaV4 S8 does not follow the established screening charge model but likely arises from the large surface reconstruction across the Jahn–Teller transition and the associated strain gradients across the domain walls. This mechanism could turn any structural, or even magnetic, domain wall conducting, if the electronic structure of the host is susceptible to local strain gradients—drastically expanding the range of materials and phenomena that may be applicable to domain wall‐based nanoelectronics. Abstract : In bulk Mott‐insulators, external pressures, or strains, are known to drive insulator–metal transitions. How this is manifested on the nanoscale, where structural domain walls are expected to have local strain gradients, is unchartered territory. This work shows that highly conductive channels arise at structural domain walls with large surface reconstruction—a proxy for strain gradients.